2019
DOI: 10.1037/cpp0000264
|View full text |Cite
|
Sign up to set email alerts
|

eSCCIP: A psychosocial ehealth intervention for parents of children with cancer.

Abstract: Objective: eHealth interventions may facilitate the dissemination of evidence-based psychosocial interventions to families of children with chronic illnesses, including cancer. This article describes a 4-phase, mixed-methods, user-centered approach to the design and evaluation of a novel psychosocial intervention for parents of children with cancer (Electronic Surviving Cancer Competently Intervention Program [eSCCIP]), adapted from an in-person intervention (Surviving Cancer Competently Intervention Program).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…The Electronic Surviving Cancer Competently Intervention Program (eSCCIP) was developed to meet the needs of POCC by offering a brief, evidence‐informed, eHealth psychosocial intervention specific to pediatric cancer 12 . Initial results suggest that the intervention is highly feasible and acceptable to POCC, and POCC have provided valuable feedback at various stages of intervention development to improve content, functionality, and recruitment/retention procedures 12,13 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Electronic Surviving Cancer Competently Intervention Program (eSCCIP) was developed to meet the needs of POCC by offering a brief, evidence‐informed, eHealth psychosocial intervention specific to pediatric cancer 12 . Initial results suggest that the intervention is highly feasible and acceptable to POCC, and POCC have provided valuable feedback at various stages of intervention development to improve content, functionality, and recruitment/retention procedures 12,13 .…”
Section: Resultsmentioning
confidence: 99%
“…The Electronic Surviving Cancer Competently Intervention Program (eSCCIP) was developed to meet the needs of POCC by offering a brief, evidence‐informed, eHealth psychosocial intervention specific to pediatric cancer 12 . Initial results suggest that the intervention is highly feasible and acceptable to POCC, and POCC have provided valuable feedback at various stages of intervention development to improve content, functionality, and recruitment/retention procedures 12,13 . In order to quickly establish an evidence base for the treatment and in an effort to shorten the timeline from intervention development to dissemination, the study team has prioritized novel study designs which allow for simultaneous collection of efficacy (eg, feasibility/acceptability) and preliminary implementation data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies investigated the impact of CH on psychosocial needs. Interventions varied, with one online Cognitive Behaviour Therapy (CBT)‐based intervention, 42 one online CBT‐based group intervention 47 and one smartphone application utilising ambient visualisation to reduce social isolation 45 . Wakefield et al‘s analysis of an online CBT intervention included measures of parental QOL, parental psychological functioning and family functioning 47 .…”
Section: Resultsmentioning
confidence: 99%
“…A main effect of time on fear of recurrence was noted, with fear of recurrence decreasing over time. One study utilised a single‐group design to examine the acceptability and feasibility of the eSCCIP online CBT‐based intervention 42 . Previous research qualitatively analysed reported social isolation of mothers of children with cancer, however the role of CH on social isolation was not examined 45 …”
Section: Resultsmentioning
confidence: 99%